2010
DOI: 10.1016/j.jorganchem.2009.11.002
|View full text |Cite
|
Sign up to set email alerts
|

New organotin(IV) complexes with l-Arginine, Nα-t-Boc-l-Arginine and l-Alanyl-l-Arginine: Synthesis, structural investigations and cytotoxic activity

Abstract: Organotin(IV) NMR Cytotoxic activity a b s t r a c tNovel diorganotin(IV) derivatives of L-Arginine (HArg), N a -(tert-Butoxycarbonyl)-L-Arginine (Boc-Arg-OH) and L-Ala-L-Arg (H 2 Ala-Arg), H 2 NC(@NH)NH(CH 2 ) 3 CH(NHR 0 )CO 2 H, where H COSY NMR spectroscopy, in solution. The spectroscopic characterization leading to the proposed molecular structures was accomplished on the basis of these experiments. L-Arginine appears to behave as a chelating ligand through carboxylate and -NH 2 groups in Me 2 Sn(Arg) 2 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…We can interpret from these data that the various tin compounds share a property that affects processes common to all cancer cell lines (i.e., increased proliferation and aberrant apoptosis). Several researchers have reported that organotin(IV) complexes have the ability to induce apoptotic cell death [52]. However, the actual mechanism of this induced apoptosis of organotin(IV) compounds has not yet been determined.…”
Section: Uptake Of Compounds 1-3 Was Detected Via Flow Cytometrymentioning
confidence: 99%
“…We can interpret from these data that the various tin compounds share a property that affects processes common to all cancer cell lines (i.e., increased proliferation and aberrant apoptosis). Several researchers have reported that organotin(IV) complexes have the ability to induce apoptotic cell death [52]. However, the actual mechanism of this induced apoptosis of organotin(IV) compounds has not yet been determined.…”
Section: Uptake Of Compounds 1-3 Was Detected Via Flow Cytometrymentioning
confidence: 99%